Hydride generation atomic fluorescence spectrometry (HG-AFS) determination of total arsenic in lipstick - E. Ghanjaoui, M.; Adraoui, I.; Gammoun, A.; Cervera, L.; El Rhazi, M.; de la Guardia, M. (International Journal of Advanced Chemistry, 2020)
This study aimed to determine the total arsenic concentration in lipsticks and evaluate the potential health risks due to daily ingestion of this toxic element from this product. The samples were analyzed using atomic fluorescence spectrometry technique after mineralization and hydride generation (HG-AFS). The calibration curve is linear over a concentration range from 0.125 to 2 Âµg L-1 with a regression coefficient of the order of 0.9899. The limit of detection is reaches 3 ng g-1. The standard deviation is of the order of 4%.The accuracy of this method was evaluated by calculating the recoveries of additions of arsenic to three lipstick samples. These results indicate recovery rates between 91% and 98%. Finely, the results found demonstrate that the method used in this work is suitable for arsenic detection in lipsticks samples.Â Â